The microbial cataclysm that forever changed life’s history - J. William Schopf (Earth History and Biodiversity)
After a full century of search, evidence of Darwin’s “missing” pre-Cambrian fossil record was finally discovered in the mid-1950s. Unsurprisingly, given the then widely held belief that Precambrian life was not only unknown but unknowable, the initial report engendered widespread skepticism. Nevertheless, new finds soon followed, discoveries that set the science on its present course by establishing the role of O2-producing phototrophic cyanobacteria as prime components of the Precambrian biota. Remarkably, however, many of the newly found ancient specimens were all but indistinguishable from cyanobacteria living today, a similarity that although bolstering their interpretation as authentic fossils raised questions about their apparent lack of evolutionary change. As the Precambrian fossil record has become increasingly better documented over recent decades, the seeming identity of modern and fossil cyanobacterial taxa has been repeatedly confirmed by workers worldwide. To accommodate these extraordinarily long-lived taxa, a new category of evolutionary rate-distribution, hypobradytely, has been added to G.G. Simpson’s classic listing and a second group of hypobradytelic Precambrian organisms, the microbial components of sulfuretum biocoenoses, has been discovered. Both of these groups originated early in earth history, the origin of O2-producing cyanobacteria ∼2700 Ma ago producing an enormous upheaval of the world’s ecosystem -- the microbial cataclysm -- as they supplanted long-established oxygen-intolerant anoxygenic photosynthetic bacteria to become the predominant primary producers, the fundament of the global ecosystem. At least three principal characteristics of these early-evolved hypobradytelic prokaryotes, both cyanobacteria and sulfuretum bacteria, have contributed to their striking differences in tempo and mode of evolution from those of the later-evolved Phanerozoic biota: (1) Their lack of outgroup biotic competition; (2) their within-group competition-minimizing ecologic preferences; and (3) their phenotype variability-limiting asexual mode of reproduction. Clearly, both the tempo and mode of evolution evolved as the cyanobacterially induced microbial cataclysm forever changed life’s history.